The Rise of the Dutch Republic $1 (BVolume 24: 1576-77s - Motley, John Lothrop, 1814-1877 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Rise of the Dutch Republic $1 (BVolume 24: 1576-77" by John Lothrop Motley is a historical account written in the mid-19th century. This work delves into the intricate political and military struggles of the Dutch Republic during the late 16th century, particularly focusing on the conflicts between the Dutch provinces and the Spanish crown. The book provides an in-depth analysis of key figures like Don John of Austria and William of Orange, traversing themes of ambition, identity, and the pursuit of freedom against authoritarian rule. In this volume, Motley unfolds the political landscape of the Netherlands amid the growing tensions of revolt against Spanish governance. Central to the narrative is Don John of Austria, whose arrival is juxtaposed against the seasoned William of Orange, who personifies the Dutch quest for independence and religious freedom. As Don John seeks to exert control with promises of conciliation while harboring ambitions for power, William's strategies of resistance and union among the provinces come to the fore. The narrative charts the complex negotiations leading to the Perpetual Edict, the failures of trust between the Dutch nobility and Spanish allegiances, and the ultimately tumultuous efforts to restore peace while laying groundwork for future insurrection$1 (Bhighlighting the precarious balance of power in the era of the Dutch revolt. (This is an automatically generated summary.)s
Release date is 2004-01-01
This eBook was produced by David Widger
Keywords: Netherlands -- History -- Eighty Years' War, 1568-1648; Netherlands -- Church history